Optimally tuned active damped dynamic vibration absorber - Rao, T.V.V.L.N. (Asian Research Publishing Network, 2016)
Vibrations can be initiated in a number of ways, and if resonances are involved, can result in very significant effects. Vibration can cause reliability problems on equipment and fatigue failures. A dynamic vibration absorber, or vibration neutralizer, is a tuned spring-mass system which reduces or eliminates the vibration of a harmonically excited system. When dynamic vibration absorber is tuned to the frequency of forced vibration of a structure, the device can completely eliminate the vibration by creating an anti-resonance at the frequency of vibration. However, any change in the frequency of vibration from the tuned frequency renders the device largely ineffective. The major drawback of the passive dynamic vibration absorber is that it is suitable only for a narrow band width of operation and therefore, it is useful in eliminating single frequency resonant vibrations. An active vibration absorber comprising a spring-mass system attached to a rigid base and an actuator utilizing the feedback taken from the absorber mass is proposed. The actuator is controlled by the feedback taken from the absorber mass itself. Optimization design of an active vibration absorber for the minimization of the resonant vibration amplitude of a single degree-of-freedom vibrating structure is derived. The effects of optimum tuning parameters on the vibration reduction of the primary structure are revealed based on the analytical model. Design parameters an active vibration absorber are optimized for the minimization of the resonant vibration amplitude of the vibrating structure. Â© 2006-2016 Asian Research Publishing Network (ARPN).